Kebijakan Turunan Pengelolaan Pendidikan Berbasis Keunggulan Lokal di Wilayah Pesisir (Studi di Dinas Pendidikan Pemuda dan Olahraga Kabupaten Aceh Utara) - Dicky Armanda (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
The policy for managing education based on local excellence in coastal areas is a policy regulated in Law No. 20 of 2003 concerning National Education and is revealed in North Aceh Qanun No. 4 of 2012 concerning the implementation of education. The problem under study is how the derivative policies on education based on local excellence and the obstacles in implementing the derivative policies for managing education based on local excellence in the coastal areas of North Aceh Regency are investigated. In this case the author uses research methods through a qualitative approach with descriptive type, data collection techniques by means of observation, interviews and documentation. and data analysis techniques, namely: data reduction, data presentation and drawing conclusions. The results of this study indicate that the form of a derivative policy of local excellence-based education management refers to the national education standard (SNP) with the form of a Dual System, Link and Match Policy which is applied to Vocational Schools. The basis for implementing education policies based on local excellence is in the form of Law No. 20 of 2003 concerning the National Education System, Aceh Qanun No. 5 of 2008 concerning the implementation of education, North Aceh Qanun No. 4 of 2012 concerning the implementation of education. The policy direction is a policy that functions of the educational unit in accordance with its nature and in relation to the surrounding environment, namely developing the potential of students in facing their role in the future according to the needs of the surrounding community. The policy direction is the development of facilities and infrastructure in accordance with the National Education Standards (SNP), Curriculum development in accordance with regional potential and in accordance with school needs and conventions from SMA to SMK.